2017
DOI: 10.1136/bmjopen-2016-015017
|View full text |Cite
|
Sign up to set email alerts
|

Is the current level of training in the use of equipment for prehospital radio communication sufficient? A cross-sectional study among prehospital physicians in Denmark

Abstract: BackgroundPhysicians working in prehospital care are expected to handle radio communication both within their own sector as well as with other divisions of the National Emergency Services. To date, no study has been conducted on the level of training received by physicians in the use of the equipment provided or on the level of competency acquired by physicians.MethodsIn order to investigate the self-assessed skill level acquired in the use of the TETRA (TErrestrial Trunked RAdio) authority radio for communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This may include routine use of "verbal priming of the radio device" such as producing a noise cue before delivery of important clinical information or improving head orientation. 36,37 Developing a future technological solution to this may be a more effective remedy. Future modifications of the existing…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may include routine use of "verbal priming of the radio device" such as producing a noise cue before delivery of important clinical information or improving head orientation. 36,37 Developing a future technological solution to this may be a more effective remedy. Future modifications of the existing…”
Section: Discussionmentioning
confidence: 99%
“…Participant comments as to the late “pickup” of DMTS (missing the start of a transmitted sentence) could be improved through radio communication training. This may include routine use of “verbal priming of the radio device” such as producing a noise cue before delivery of important clinical information or improving head orientation 36,37 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the compatibility of communication systems between different authorities and sectors 70,71 may present a barrier to MI communication, for example, between military and civilian authorities related to secrecy and encryption. Simulation training in the use of radio communication has not been utilized extensively, 73 whereas simulations in prehospital trauma care 74 and ultrasound, 75,76 for example, are widely implemented with significantly improved performance after completing training. In the study by Holm, 72 implementation of a simulation is recommended for improvement of communication skills.…”
Section: Communication Systems Overload and Incompatibilitymentioning
confidence: 99%
“…Based on 450 interviews of police, fire & rescue, EMCC, and EMS personnel, it was evident that knowledge and experience were varying, and especially the EMS personnel and the EMCC personnel used SINE in a restricted manner that did not fully utilize the options and possibilities of the system. A study by Holm [25] among Danish prehospital physicians concluded that initial training in the use of communication devices had not been prioritized as highly as other technical skills, but found the training level to be sufficient for everyday use for the majority of users. For a substantial minority, however, further training was considered necessary.…”
Section: Communicationmentioning
confidence: 99%